Morphology and Internal Mixing of Atmospheric Particles - Claudio Mazzoleni (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The properties of atmospheric particles - often also termed aerosol - have been the subject of scientific studies for several decades because of their effects on air quality, health, visibility, propagation of electromagnetic radiation in the atmosphere, and climate. However, despite intense research efforts, several knowledge gaps remain to be filled; the reason being related also to the complexity of the physical and chemical characteristics of these particles and of their dynamic interactions with the surrounding environment. One of the frontier topics in this scientific endeavor is the subject of this special issue: the morphology and mixing of atmospheric aerosol at the single particle level.